A new diploid species belonging to the Odontophrynus americanus species group (Anura: Odontophrynidae) from the Espinhaço range, Brazil - Carvalho Rocha, Pedro (2017)
Fil: Carvalho Rocha, Pedro. Universidad Federal de Minas Gerais. Instituto de Ciencias Biológicas. Departamento de Zoologia. Laboratório de Herpetologia; Brasil.